Hot spot stress investigation on rib-to-deck-to-floor beam connections in UHPC reinforced OSDs. (April 2021) - Cheng, Bin; Abdelbaset, Hesham; Tian, Liang; Li, Hai-Ting; Su, Qingtian
Abstract: Orthotropic Steel Decks (OSDs) are widely used in various steel bridge types and however, their fatigue performances remain a prominent issue. In this paper, experimental work was conducted to investigate the hot spot stresses at various details of rib-to-deck-to-floor beam (RDF) welded connection in OSDs reinforced by ultra-high-performance concrete (UHPC). Quadratic extrapolation approach was applied to determine the hot spot stresses at weld toes of different fatigue prone details according to IIW specifications. Parametric studies were performed using finite element analysis to examine the effect of structural key parameters on the hot spot stresses including UHPC layer thickness and UHPC elastic modulus. Experimental results indicated that longitudinal flexural increased the out-of-plane distortions of the U-rib walls, therefore the hot spot stresses at locations on the U-rib were remarkably higher than that around floor beam cut-out. It is observed that hot spot stresses at region A on the U-rib wall directly under the acting load were controlled by tensile stresses, while region B on the other side of the acting load had compression stresses. The application of 60 mm UHPC layer significantly reduced the hot spot stresses at critical location on the U-rib and around floor beam cut-out by 57.8% and 36.5%, respectively. Parametric study results demonstrated that increasing UHPC layer thickness significantly reduced the hot spot stresses at all considered locations, while increasing the elastic modulus of UHPC layer slightly influenced the hot spot stresses and its effect can be neglected. Highlights: Static tests of rib-to-deck-to-floor beam (RDF) welded connections in UHPC reinforced orthotropic steel decks were conducted. Hot spot stresses at critical locations of RDF welded connection due to longitudinal flexural of the deck were investigated. Effects of employing UHPC overlay on decreasing hot spot stresses in OSDs was evaluated. The effects of structural key parameters on the hot spot stresses of RDF welded connections were numerically assessed.